A motivational interview intervention delivered at home to improve the oral health literacy and reduce the morbidity of Chilean disadvantaged families: a study protocol for a community trial. Issue 7 (13th July 2017) - Cartes-Velasquez, Ricardo; Araya, Carlos; Flores, Raúl; Luengo, Luis; Castillo, Francisca; Bustos, Alex
Abstract : Introduction: Oral health education/promotion interventions have been identified as cost-efficient tools to improve the oral health of the population. These interventions are regularly made in contexts where the target population is captive, for example, in health centres. In Chile, there are no oral health interventions delivered at home. Methods and analysis: This community trial covers two disadvantaged urban areas in the province of Concepción. Both sectors have public preschool education coverage with a traditional programme (TP) to promote oral health. The intervention will comprise four to six visits by dental hygienists trained in the delivery of a standardised oral health promotion programme using motivational interviewing (MI) at home. The experimental group will receive TP and MI, while the control group will receive only TP. If a positive and significant effect of MI is found, this will be administered to the control group. For a 50% reduction in the incidence of caries, a sample size of 120 preschoolers per group is estimated. Data will be gathered on demographic and socioeconomic variables; oral health outcomes using WHO oral health indicators (the prevalence and severity of caries, periodontal disease, dentofacial anomalies and oral hygiene); the oral health literacy of caregivers, measured by the Rapid Estimation of Adult Literacy in Dentistry and the Oral Health Literacy Instrument, both validated for the Chilean population. Assessments will take place at baseline and at 12-month follow-up. Ethics and dissemination: The university bioethics committee approved this study (EI/21/2014). We will submit the trial's results for presentation at international scientific meetings and to peer-reviewed journals. Trial registration number: ACTRN12615000450516.